2011
DOI: 10.1016/j.carres.2011.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-(1→6)-linked N-acetyl-d-glucosamine oligosaccharide substrates and their hydrolysis by Dispersin B

Abstract: Dispersin B (DspB) from Aggregatibacter actinomycetemcomitans is a β-hexosaminidase exhibiting biofilm detachment activity. A series of β-(1→6)-linked N-acetyl-D-glucosamine thiophenyl glycosides with degree of polymerisation (DP) of 2, 3, 4 and 5 were synthesized, and substrate specificity of DspB was studied on the obtained oligosaccharides. For oligomer synthesis a 1+2, 2+2, 1+4 coupling strategy was applied, using bromo-sugars as glycosyl donors. The formation of 1,2-trans interglycosidic bond has been ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…Furthermore, Bb -GH and Ec -GH lack hydrolytic activity on p NP-glycoside substrates and short PNAG oligomers and contain a pronounced and well-conserved substrate-binding groove suited to binding long stretches of polymer [ 24 ]. This is in contrast to the only other characterized PNAG hydrolase, DspB, which displays both exo and endo -acting hydrolysis of PNAG and has a shallow substrate-binding groove [ 53 , 54 ]. However, it does correlate with the bacterial cellulose and Psl biosynthesis systems, as BcsZ and PslG are both endo -acting glycoside hydrolases with long and deep substrate-binding clefts [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, Bb -GH and Ec -GH lack hydrolytic activity on p NP-glycoside substrates and short PNAG oligomers and contain a pronounced and well-conserved substrate-binding groove suited to binding long stretches of polymer [ 24 ]. This is in contrast to the only other characterized PNAG hydrolase, DspB, which displays both exo and endo -acting hydrolysis of PNAG and has a shallow substrate-binding groove [ 53 , 54 ]. However, it does correlate with the bacterial cellulose and Psl biosynthesis systems, as BcsZ and PslG are both endo -acting glycoside hydrolases with long and deep substrate-binding clefts [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, microorganisms themselves utilize specific glycoside hydrolases to initiate dispersal events. For example, dispersin B is a ␤-hexosaminidase produced by the Gram-negative bacterium Aggregatibacter actinomycetemcomitans in order to disperse adherent cells from a mature biofilm (12). It has been shown that exogenous addition of dispersin B is capable of preventing and disrupting biofilms in vitro and in vivo (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Fluorescence-labeled hexasaccharide as a substrate for the processing enzymeglucosidase I. Facile synthesis of 1,2-cis glucosidic linkage (Iino et al, 2012) Glycosaminoglycan disaccharides TOF Use of a glucuronate glycosyl donor with a 2-O-acyl-6,3-lactone structure (Furukawa et al, 2011b) -Glycosyl amides TOF Synthesis from N-glycosyl dinitrobenzenesulfonamides (Gaitonde & Sucheck, 2012) Glycosyl disulfides MALDI (DHB) -glycosyl disulfides prepared in a few hours from per-O-Ac precursors (Adinolfi et al, 2011) -Glycosyl imidinium triflate TOF Elaboration to disarmed-armed iterative glycosylation (Lin et al, 2012c) Heparosan oligosaccharides TOF (DHB) Synthesis by Pasteurella multocida PmHS2 single-action transferases (Chavaroche et al, 2012) Chitosan oligosaccharides Effects on activation of murine spleen CD11c+ dendritic cells via toll-like receptor 4 TOF (Fekete et al, 2011) Low-MW chitosan oligosaccharides TOF By chitosanase hydrolysis of chitosan. Anti-inflammatory effects (Chung et al, 2012a) Mannosides with hydrophobic substituents TOF Synthesis as DC-SIGN antagonists (Obermajer et al, 2011) 15 N, 13 C 2 8-sialic acid oligomers TOF Evidence for helical structure in a tetramer of 2 8 sialic acid (Battistel et al, 2012) Oligo( -D-glycosyl phosphate) derivatives TOF Use of a phosphoramidite method via boranophosphate intermediates (Fujita et al, 2011b) Orthogonally protected disaccharide MALDI For synthesis of 6-sulfated derivatives with terminal ethylamine (Liu et al, 2012g) Pustulooligosaccharides ( (Yang et al, 2011f) Tri-, penta-, and heptasaccharides, with orthogonally N-protected amino residues TOF Synthesis of four bifunctionalized orthogonally N-protected oligosaccharides derived from lactose and mannose, intended as cross-linking derivatives (Fyrner et al, 2012a) Poly-N-acetyllactosamineextended TOF (DHB) For recognition studies by human and avian influenza A virus hemagglutinins …”
Section: Tof (Dhb) Chiral Separation Of Catechin By Capillary Electromentioning
confidence: 99%